Influence of dielectric stiffness, interface, and layer thickness on hysteresis loops of ferroelectric superlattices - Chew, Khian Hooi; Iwata, M.; Ong, L.H. (2011)
We examined the influence of dielectric stiffness, interface, and layer thickness on the hysteresis loops, including the remanent polarization and coercive field of a superlattice comprising alternate layers of ferroelectric and dielectric, using the Landau-Ginzburg theory. An interface energy term is introduced in the free energy functional to describe the formation of interface "dead" layers that are mutually coupled through polarization (or induced-polarization). Our studies reveal that the hysteresis loop is strongly dependent on the stiffness of the dielectric layer, the strength of the interface coupling and layer thickness. The intrinsic coupling at the interface between two neighboring layers reduces the coercive field, though the corresponding remanent polarization is significantly enhanced by a soft dielectric layer. (C) 2011 American Institute of Physics. [doi:10.1063/1.3630016]